Protocol: Systematic Literature Review about B-Corp - Elsa Diez-Busto; Lidia Sanchez-Ruiz; Ana Fernandez-Laviada (WPOM : Working Papers on Operations Management)
The B Corp movement is becoming increasingly important nationally and internationally. In fact, the number of certified companies has radically increased (34,78%) from 2017 (2300 B-Corp companies) to 2019 (3100 B-Corp companies). Taking this fact into consideration, the aim of this study is to present a research protocol for conducting a systematic review of literature on B Corp companies. First, the inclusion and exclusion criteria applied that allow reaching the final sample of 45 articles are specified. The codes that will be used in the analysis phase are also made explicit.